PENGARUH CAPITAL STRUCTURE DAN FIRM SIZE TERHADAP AGENCY COST DAN KINERJA KEUANGAN - Poppy Pujawati; Ni Ketut Surasni (Master of Management, Mataram University, 2020)
This research is aimed at examining the effect of capital structure and firm size on agencycost and financialperformanceofMiscellaneous Industrywhich listed in BEI. The populations of this research were all Miscellaneous Industrywhich listed in BEI.Sampling was conducted using a purposivesampling method so that in this research the number ofsamples were 23 companies in the 2013-2017 period.Testing classic assumptions include normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The collected data werethen analyzed with path analysisusing SPSSprogram and Sobel test. The research showed that there is an influence of the firm size tested has an effect on agency cost, while the capital structure has not an effect on agency cost. There is an influence of firm size, and agency cost on financial performance, while the capital structure has not an effect on the financialperformance. There is an indirect effect of firm size on financial performance through agency cost as an intervening variable.Keywords: Capital Structure, Firm Size, Agency Cost, Financial Performance.